Helium isotope separation driven by heat flux in Helium II (Heat-Flush Method) - Qianxi Qu; Huan Chen; Yiqun Chu; Weipeng Xu; Laifeng Li; Peng Jia; Dong Xu (International Journal of Refrigeration, 2026)

Flow visualization study of superleak filtration for helium isotope separation - Qianxi Qu; Huan Chen; Weipeng Xu; Yiqun Chu; Laifeng Li; Peng Jia; Liguo Wang; Dong Xu (International Journal of Refrigeration, 2026)

Agricultural expansion since the Qin–Han dynasties intensified dust activity in inland China - Fuyuan Gao; Junhuai Yang; Linkai Wang; Kaiming Li; Lai Zhao; Xin Liu; Haoyu Wang; Wenxi Qu; Jiaxin Zhou; Dongyu Jia; Xiaoying Nie; Qiuyue Sun; et al. (Global and Planetary Change, 2026)

Computational study on the hydrothermal cracking routes of N-cyclohexylnaphthalen-1-amine based on density functional theory - Shao-Xuan Zhong; Wei Li; Jia-Wei Qu; Ming-Lan Ge; Yuan-Liang Yang; Jian-Qiang Tao; Jing Wang (Fuel, 2026)

Gold nanocluster-tuned S-scheme porphyrin COF heterojunction leveraging interface electron bridge for near-infrared-triggered phototherapy - Yong Lu; Chunyan Fang; Wenqing Jia; Shuang Liu; Qiang Wang; Chunsheng Li; Jiawei Qu; Peiyao Wang; Hui Zhang; Hongying Ge; Fuyu Wang; Jiating Xu (Chemical Engineering Journal, 2026)

Simultaneous interlayer expansion and surface ion-conductive coating for high-rate graphite anodes - Liming Zhang; Gang Chen; Zhihu Wang; Changming Qu; Longfei Li; Chengyu Fu; Wenwen Deng; Baozhang Li; Yi Sun; Jia-Wei Wang; Hongfa Xiang; Xuyong Feng (Chemical Engineering Journal, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Thermodynamic rebalancing of dissociation-coordination effect in weakly solvating electrolytes for high-performance sodium-ion batteries - Yan Meng; Yuanheng Wang; Qingjiang Liu; Hongji Pan; Jinghao Zhao; Xinhao Qu; Jia-Yan Liang; Xin Li (Chemical Engineering Journal, 2026)

Corrigendum to “In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota” [Carbohydrate Polymers 339 (2024) 122255] - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2026)

Comprehensive epigenetic landscape of Sulfur Mustard (SM) exposure in HaCaT keratinocytes - Yuejia Du; Bo Ma; Yuanjie Li; Yanli Zhu; Zhi Li; Minmin Qu; Qinyun Shi; Weiwei He; Jia Chen; Bin Xu; Jie Li; Wenqi Meng; et al. (Chemico-Biological Interactions, 2026)

Altered gray matter network segregation and disrupted interregional connectivity in children with persistent developmental stuttering: a graph-theoretical morphometric study - Wanqing Liu; Dan Ma; Chuanlong Cao; Sai Liu; XinMao Ma; Fenglin Jia; Pei Li; Hui Zhang; Yimin Hua; Yi Liao; Haibo Qu (Brain Imaging and Behavior, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Experimental investigation of trace helium-3 enrichment via total-reflux cryogenic distillation in a 2 K cryostat - Huan Chen; Peng Jia; Weipeng Xu; Qianxi Qu; Yiqun Chu; Dong Xu; Liguo Wang; Laifeng Li; Xiaoqin Zhi (International Journal of Refrigeration, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Selenium nanoparticles alleviate chromium stress in wheat (Triticum aestivum L.) by inhibiting root uptake, enhancing antioxidant capacity, and regulating the rhizosphere microbiome - Lili Qu; Hanchi Liu; Jia Li; Xin Li; Ran Chen; Xin Liang; Xuewei Jia; Pan Wu; Xiaohui Qiao; Chunping Xu (Journal of Environmental Management, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Unlocking Gut Health: Evaluation of Structure and Characteristics of Astragalus Polysaccharides Modified by Lactic Acid Bacteria Fermentation - Pengshuo Yang; Qing Zhou; Mingyue Jia; Kelin Li; Qingsong Qu; Weishuo Ren; Xinhui Peng; Guoqing Li; Yueyang Xie; Bingxuan Li; Xinyuan Shi (Probiotics and Antimicrobial Proteins, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First mapping of subsurface soil temperature profiles by integrating diurnal cycles of microwave and thermal infrared observations - Dabiao Chen; Huazhu Xue; Tianjie Zhao; Yuyang Xiong; Ning Li; Jingyao Zheng; Yipeng Cao; Yu Bai; Songbo Qu; Ling Yao; Tang Liu; Chi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Synergistic photobiocatalytic antifouling strategy based on a Bi5O7I/CeO2 heterojunction for sustainable marine coating - Bingqing Jia; Ting Xu; Qian Zhang; Xudong Geng; Jiachen Xu; Yuezheng Li; Yuanyuan Qu; Xiangdong Liu; Mingwen Zhao; Weifeng Li; Yong-Qiang Li (Chemical Engineering Journal, 2026)

Targeting methionine-induced pyroptosis enhances anti-tumor immunity - Mingzhu Lei; Wenying Zhu; Chao Wang; Fan Zhang; Miaolin Li; Yi Zhang; Jia Qu; Zhiguo Luo; Jintao Li; Zeng-Xia Li; Miao Yin; Qun-Ying Lei (Science China Life Sciences, 2026)

The contributions of two fertilization events to the fertilization recovery efficiency in Arabidopsis - Yuan Wang; Yaxiao Liu; Wenhao Li; Han Lu; Li-Jia Qu; Sheng Zhong (Science China Life Sciences, 2026)

Study on crop coefficient of vegetation in cold and high-altitude regions based on lysimeter measurements - Liuyan Qu; Runjie Li; Shaofeng Jia; Zhanyi Gao; Haorui Chen (Irrigation Science, 2026)

The unique biogenesis pathway of extracellular vesicles in Hirudo nipponia salivary gland cells - Ya-Li Zhu; Meng-Xiang Jia; Ru-Yu Qu; Qian Li; Xia Qiu; Wen-Chen Zhao; Yuan-Yuan Luo (Tissue and Cell, 2026)

Interfacial synergy-enhanced catalysis in hierarchically confined poly (glycidyl methacrylate) @ZIF-8@Au composite microspheres for p-nitrophenol degradation - Jian-Bo Qu; Guo-Yu Yue; Jian-Ling Zhang; Yuan Yang; Dong Wang; Jia-Le An; Jing Li (Journal of Environmental Chemical Engineering, 2026)

Fabrication of chitosan/alginate/angelica polysaccharide functional microcapsules: enhancing the viability of Lactobacillus paracasei in digestion, storage and applications - Haifu Jia; Jinghang Zhang; Yuanyuan Li; Zhishan Song; Yatong Ni; Bo Qu; Xinyan Yang; Qianyu Zhao; Yujun Jiang (Food Hydrocolloids, 2026)

Valorization of oily sludge with coal gasification slag via catalytic pyrolysis - Lei Han; Hai-Jie Hu; Jia-Xuan Liu; Tao Yu; Jin-Ling Li; Lan-Ting Ma; Cheng-Tun Qu; Zhong-Wen Liu (Bioresource Technology, 2026)

Applicability assessment of molecular tools and identification of lines suitable for genetic transformation in the red alga Pyropia yezoensis - Xuexue Cao; Jiaxin Qu; Jia hui Sun; Yichi Li; Ying Sun; Yunxiang Mao; Fanna Kong (Algae, 2026)
Pyropia yezoensis, a red macroalga distributed in the intertidal zone, serves as an important model organism for studying the adaptive mechanisms of intertidal seaweeds in response to abiotic stressors. Additionally, it is a significant economic seaweed due to its high nutrient content and is widely cultivated in China, Japan, and Korea. Despite its importance, existing molecular tools for genetic transformation remain limited and require further development to enhance our understanding of P. yezoensis biology. To address this limitation, based on previous studies, we firstly evaluated the expression of eight fluorescent proteins (FPs) in P. yezoensis. Our findings confirmed that PyZsYellow, PyZsGFP, and PysGFP can be detected successfully their specific fluorescent signals within the cells of P. yezoensis thalli. Notably, PyZsGFP demonstrated effectiveness in sporophytic filaments. 2×SV40 and PyNP may function as nuclear localization signal sequences, effectively directing the FP to localize within the nucleus of cells in P. yezoensis. T2A linker can mediate protein cleavage, to express the multiple genes in one construct, enabling them to function independently in P. yezoensis. Furthermore, we identified that the RZ line exhibited the highest transformation potential, while the middle region of thalli showed the superior transformation efficiency. A significant correlation between cell size and transformation efficiency. These findings will contribute to developing a systematic toolkit for conducting genetic transformations and elucidating gene functions in P. yezoensis.

Design and Optimization of Indomethacin Nanocrystals using Machine Learning and Molecular Dynamics Simulations - Jianlu Qu; Chaoliang Jia; Yaobin Chen; Haibin Qu; Wenlong Li (AAPS PharmSciTech, 2026)

Ice-induced response prediction of offshore platforms via virtual-to-field data-driven modeling under scarce data conditions - Ziguang Jia; Xin Wang; Wei Li; Sichong Ma; Kuankuan Wu; Yan Qu (Ocean Engineering, 2026)

Atmospheric pollution is associated with microbial community stability and functional diversity in river ecosystems - Yuying Jia; Xiangang Hu; Qian Qu; Li Mu (Environmental Pollution, 2026)

Bimetallic synergism-driven Au0.75Pt0.25 nanoparticles-modified SnO2 heterojunction nanostructures for ultrasensitive detection of carbonate-based electrolyte leakage gases towards battery safety applications - PeiJiang Cao; LinLong Qu; YuWei Li; Fang Jia; YuXiang Zeng; DeLiang Zhu; ChunFeng Wang; Shun Han; Ming Fang; XinKe Liu; WenJun Liu; Sachin T. Navale (Chemical Engineering Journal, 2026)

Total synthesis of marine cyclopeptide largamides B and H, and tiglicamide B - Youzhi Li; Yuzhao Chen; Shuo Liang; Shiwei Qu; Jia-Lei Yan; Tao Ye; Zhongliang Dai (Molecular Diversity, 2026)

Numerical Study of Lateral Layout in Multilateral Wells for Depressurization of Class 1 Hydrate Reservoirs with Boundary Sealing - Tinghui Wan; Zhanzhao Li; Qi Li; Jia Qu; Changrong Xiao; Jingli Wang (Journal of Marine Science and Engineering, 2026)
Efficient development of marine natural gas hydrates (NGHs) remains challenging. Employing depressurization combined with complex structured wells and reservoir stimulation techniques is one of the key approaches to enhancing production. This study aims to theoretically evaluate the production response of different lateral layouts of multilateral wells under the conceptual condition of an idealized boundary sealing for the depressurization exploitation of Class 1 hydrate reservoirs. Based on data from China’s first offshore trial production, a numerical simulation method was used to systematically compare the development performance of various lateral layouts integrated with boundary sealing. Under the idealized modeling scenario, the simulation results indicate that the low-permeability barrier formed by boundary sealing can significantly suppress water invasion, promote pressure propagation, and thereby improve productivity. More importantly, optimizing the lateral layout can further enhance gas production performance. Under boundary sealing conditions, Case 8B with six downward-deployed laterals, compared to Case 1A without sealing and with six laterals in a planar staggered layout, its cumulative gas production (1733.75 × 104 m3) was 2.08 times that of Case 1A (831.68 × 104 m3), and its gas-to-water ratio (327.64) was 1.62 times that of Case 1A (202.09). This indicates that under boundary sealing conditions, lateral layout is one of the key levers to improve productivity. Under the modeling assumptions of this work, the research findings can provide a theoretical reference for evaluating the development of Class 1 hydrate reservoirs with multilateral wells where boundary sealing is considered.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

Monascus fermentation enhances the lipid-lowering properties of ginseng in vivo and component assay - Qingsong Qu; Qing Zhou; Xinhui Peng; Zhixun Li; Mingyue Jia; Yingying Zhang; Cuiting Yang; Xingxing Dai; Mengke Sheng; Jichuan Kang; Xinyuan Shi (Food Research International, 2026)

Study on the effect of glycosylation reaction in wet mixing on the emulsifying properties of extensively whey protein hydrolysates - Zhen Huang; Lidong Pang; Runze Li; Jia Shi; Qianyu Zhao; Yujun Jiang; Xinyan Yang; Bo Qu (Food Chemistry, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Development of Curcumin Nanosuspension Micro-Pellets Using Hummer Acoustic Resonance and Fluidized Bed Coating - Chaoliang Jia; Jianlu Qu; Taoning Liu; Wei Wu; wenlong Li (Journal of Pharmaceutical Innovation, 2026)

Identification of stomatal opening positive regulators in augustinegrass - Dong-Li Hao; Jia Qu; Jun-Qin Zong; Zhi-Yong Wang; Jiang-Shan Hao; Hai-Long Lu; Ying Zhao; Dao-Jin Sun; Sheng-Nan Yang; Jian-Xiu Liu; Li Liao; Ling Li (Horticulture, Environment, and Biotechnology, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Improvement of Growth and Selenium Absorption Characteristics of Tomato Plant by Lactic Acid Bacterial Biochar Fertilizer - Haifeng Li; YuXuan Su; Guanglong Wu; Yiming Zhang; Feng Jia; Xifeng Wang; Jianhang Qu (Current Microbiology, 2026)

CYP450 activation and mitophagy induction mediate Ti3C2 MXene detoxification in RAW 264.7 cells - Yujiao Liu; Xuan Mao; Yongyi Wei; Xiaodi Li; Jianbo Jia; Qingmeng Liu; Jian Liu; Yu Wang; Xiaofei Zhou; Huihui Wang; Jingbo Pi; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Synthesis, properties, and separation applications of MXenes/COFs composites: A review - Jiahao Li; Yanqing Qu; Xiaoyu Du; Hongge Jia; Shuangping Xu; Mingyu Zhang (Journal of Environmental Chemical Engineering, 2025)

Enhanced tetracycline hydrochloride removal by ultra-microporous phosphorus-doped KOH-activated microalgal biochar: Adsorption performance and mechanistic insights - Bing Liu; Weihao Li; Yiwen Huang; Wenli Qin; Min Wang; Yang Jia; Hanqing Xu; Liyin Qu; Hongbin Jiang; Chao Wang; Zengling Ma (Environmental Research, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

Inducing fast-growth and high drought tolerance in Zoysia matrella via cold plasma-irradiated callus - Ling Li; Dongli Hao; Haoran Wang; Shengnan Yang; Jia Qu; Jianjian Li; Hailin Guo; Xiaohui Li; Hailong Lu; Junqin Zong (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Measuring the spatial structure of cold island and carbon sequestration networks and their interactions in urban agglomerations: a motif and multilayer network analysis perspective - Chen Qu; Jia Xu; Wen Li; Song Shi; YuCen Zhai (Sustainable Cities and Society, 2025)

Synergistic air pollution and CO2 emission reduction in China's iron and steel industry based on real-time monitoring data - Ling Tang; Qing Yu; Jiabao Qu; Ruxing Wan; Min Jia; Shuangyue Qian; Song Lv; Jieyi Li; Shuo Qi (Environmental Pollution, 2025)

Mechanical properties of waterbomb origami tubes with enhanced energy absorption and crushing efficiency - Xiang Jie Wei; Yi Zhang; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Xiao Ji; Tao Ding; Jia Hui Zhang; Lin Hua; Wei Shen; Xin Ren (Engineering Structures, 2025)

A novel strain-based deformation monitoring method for subsea free-spanning pipelines - Tao Jiang; Zi-min Xie; Jia-jian Wang; Dong-sheng Li; Chun-xu Qu (Engineering Structures, 2025)

SnRNA-seq Interprets Mechanisms by which Three Glial Cell Types Influence Myelin Regeneration in Adult Drug-Resistant Epilepsy-Related Cognitive Impairment - Lu Wang; Jia-Qi Ma; Yong-Qian Bian; Xiao-Peng Qu; Yue Zhang; Chao Wang; Guo-Dong Gao; Long-Long Zheng; Qi-Xing Fang; Li-Jia Song; Liang-Liang Shen; Bei Liu (Molecular Neurobiology, 2025)
Myelin regeneration has been shown in previous studies to ameliorate varying degrees of cognitive impairment in patients with neurodegenerative disorders such as epilepsy. The problem of myelin regeneration in adults with drug-resistant status epilepticus is a major key to the difficulty of treating cognitive impairment in adults with drug-resistant epilepsy (DRE). The purpose of this study is to provide a molecular map of myelin-related molecules under the cognitive deficits seen in DRE. We used a lamotrigine-pentylenetetrazol-resistant epilepsy mouse model and verified the cognitive problems and myelin changes using a water maze and conventional molecular biology techniques. We then analyzed the OLs in the hippocampus of the mice and the effect on myelin using sn RNA-seq technology. We found that the problem of cognitive impairment in drug-resistant epileptic mice is due to altered myelin plasticity. OL maturation induces pathological myelin regeneration which ultimately leads to cognitive impairment. The three glial cell types are closely related to the occurrence of myelin regeneration and jointly promote pathological myelin regeneration. Our study revealed the presence of myelin regeneration in DRE. All of this evidence suggests that normal myelin regeneration contributes to cognitive impairment improvement, but pathological myelin regeneration impairs cognition. Graphical Abstract Schematic representation of myelin regeneration in cognitive impairment in adult drug-resistant epilepsy. Boxed are pathways or molecules related to the promotion of myelin regeneration in which a subpopulation is involved. Red font indicates promotion, blue font indicates inhibition, and gray font indicates unknown but relevant.

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Corrigendum to ‘Molecular and carbon isotopic geochemistry of oils with different fluorescence color from the Upper Jurassic Qigu formation and oil accumulation process in Yongjin area, Junggar Basin in China’ [J. Mar. Petrol. Geol. 171 (2024) 107163] - Hongrui Zhang; Hua Liu; Wanglu Jia; Hui Tian; Jinbu Li; Shuang Yu; Yansheng Qu; Xiangyu Meng (Marine and Petroleum Geology, 2025)

Smartphone-assisted ultrasensitive colorimetric strategy based on Cu-CN single-atom nanozyme for acrylamide detection in fried food - Jia Ge; Xiaoyu Sun; Xinxin Li; Yu Yang; Lin Zhang; Lingbo Qu; Zhaohui Li (Food Chemistry, 2025)

Stepwise enolization and coordination enabling dual redox-active carbonyl-imidazole based π-conjugated polymer anode for potassium ion batteries - Zhikai Deng; Yongqiang Li; Wensheng Tian; Xueqi Zhao; Maoda Qu; Xinlin Wan; Nengqin Jia; Yang Chen (Chemical Engineering Journal, 2025)

Magic cube metamaterials - Zuntian Chu; Xinqi Cai; Ruichao Zhu; Tonghao Liu; Huiting Sun; Fan Wu; Tiefu Li; Yuxiang Jia; Yajuan Han; Shaobo Qu; Tiejun Cui; Jiafu Wang (Science Bulletin, 2025)

The relationship between physical property evolution and reservoir formation in volcanic rock reservoirs: The Huoshiling Formation, Dehui Fault Depression, southern Songliao Basin - Liang Liu; Jijun Li; Tianhong Yang; Libin Song; Kexin Jia; Lili Li; Weiwei Qu; Jun Jiang; Shikai Ni; Chenghong Luo (Marine and Petroleum Geology, 2025)

Typhoon fragility analysis of transmission tower-line system considering wind-induced fatigue - Jia-Xiang Li; Tong Yang; Chao Zhang; Li Sun; Chun-Xu Qu (Engineering Structures, 2025)

Spatial organization and trafficking dynamics of ANX/BUPS-RALF-LLG signaling complexes during pollen tube growth - Patricia L. Seitz; Li-Jia Qu; Thomas Dresselhaus; Liang-Zi Zhou (Plant Reproduction, 2025)

TSC2/mTORC1 integrates deoxynivalenol signals recognized by membrane receptors IR and EGFR to restrict intestinal stem cell function - Cai-xia Dou; Hao-zhan Qu; Ying-chao Qin; Xiao-fan Wang; Hui-chao Yan; Run-sheng Li; Yu-guang Zhao; Jia-yi Zhou; Xiu-qi Wang (Journal of Hazardous Materials, 2025)

Accelerating enrichment of ARGs and MGEs with increasing ammonium removal during partial nitrification treating high-strength ammonia wastewater - Heng Yu; Weiyi Jia; Yuqiu Luo; Rong Zhang; Junkai Zhao; Cong Lu; Yue Dong; Shuo han; Bing Li; Chengtun Qu (Environmental Research, 2025)

Quantifying the nonlinear effects of urban-rural blue-green landscape combination patterns on the trade-off between carbon sinks and surface temperature: An approach based on self-organizing mapping and interpretable machine learning - Chen Qu; Jia Xu; Wen Li; Song Shi; Baozhu Liu (Sustainable Cities and Society, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Genome-wide identification and functional characterization of the Shaker potassium channel family in centipedegrass suggest their distinct roles in potassium uptake and salt tolerance - Dong-Li Hao; Jin-Yan Zhou; Jia Qu; Jun-Yi Zhai; Ying Zhao; Jian-Xiu Liu; Hai-Lin Guo; Jun-Qin Zong (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Fermentation interactions and lipid-lowering potential of Monascus purpureus fermented Ginseng - Cuiting Yang; Yingying Zhang; Mingyue Jia; Qingsong Qu; Zhixun Li; Qing Zhou; Minfang Feng; Yuting Tian; Weishuo Ren; Xinyuan Shi (Food Bioscience, 2025)

Progress in separation and detection of foodborne bacteria for food safety - Lei Wang; Kaiyuan Jia; Xiaoyun Qu; Yanbin Li; Jianhan Lin (Current Opinion in Food Science, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Replication factor C4, which is regulated by insulin-like growth factor 2 mRNA binding protein 2, enhances the radioresistance of breast cancer by promoting the stemness of tumor cells - Xiao-Yu Zhu; Pi-Song Li; Hui Qu; Xing Ai; Zi-Ting Zhao; Jia-Bei He (Human Cell, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Molecular and carbon isotopic geochemistry of oils with different fluorescence color from the Upper Jurassic Qigu formation and oil accumulation process in Yongjin area, Junggar Basin in China - Hongrui Zhang; Hua Liu; Wanglu Jia; Hui Tian; Jinbu Li; Shuang Yu; Yansheng Qu; Xiangyu Meng (Marine and Petroleum Geology, 2025)

Factors affecting the different growth rates of PM2.5：Evidence from composition variation, formation mechanisms, and importance analysis of water-soluble inorganic ions with case study in northern China - Huan Li; Ting Zhang; Hui Su; Sui Xin Liu; Ying Qiang Shi; Lu Yao Wang; Dong Dong Xu; Jia Mao Zhou; Zhu Zi Zhao; Qi Yuan Wang; Steven Sai Hang Ho; Yao Qu; et al. (Atmospheric Environment, 2025)

Assessment of myelination development in neonatal rats using chemical exchange saturation transfer (CEST) 7-T MRI - Rui Wang; Shuxian Xu; Fenglin Jia; Yi Liao; Jiayi Li; Jing Liu; Fengyan Zhao; Haibo Qu (Experimental Brain Research, 2025)

Exploring the Prebiotic Potential of Fermented Astragalus Polysaccharides on Gut Microbiota Regulation In Vitro - Pengshuo Yang; Qing Zhou; Yingying Zhang; Mingyue Jia; Runshuang Li; Qingsong Qu; Zhixun Li; Minfang Feng; Yuting Tian; Weishuo Ren; Xinhui Peng; Xinyuan Shi (Current Microbiology, 2025)

Better prediction of greenhouse extreme temperature base on improved loss function - Yunsong Jia; Li’ao Qu; Shuaiqi Huang; Xin Chen; Xiang Li (Computers and Electronics in Agriculture, 2024)

Water and nitrogen coupling regulates the present and future restoration trends under Spartina alterniflora invasion in a coastal salt marsh - Peng Jia; Guojuan Qu; Jing Jia; Haowen Xu; Dezhi Li (Ecological Engineering, 2024)

Analysis of PANoptosis-related ceRNA network reveals lncRNA MIR17HG involved in osteogenic differentiation inhibition impaired by tumor necrosis factor-α - Jia-Xuan Li; Yu-Dun Qu; Chang-Liang Xia; Wei Zhang; Song-Song Wang; Shuan-Ji Ou; Yang Yang; Yong Qi; Chang-Peng Xu (Molecular Biology Reports, 2024)
Background Inflammatory cytokines such as Interleukin 1β(IL1β), IL6,Tumor Necrosis Factor-α (TNF-α) can inhibit osteoblast differentiation and induce osteoblast apoptosis. PANoptosis, a newly identified type of programmed cell death (PCD), may be influenced by long noncoding RNA (lncRNAs) which play important roles in regulating inflammation. However, the potential role of lncRNAs in inflammation and PANoptosis during osteogenic differentiation remains unclear. This study aimed to investigate the regulatory functions of lncRNAs in inflammation and apoptosis during osteogenic differentiation. Methods and results High-throughput sequencing was used to identify differentially expressed genes involved in osteoblast differentiation under inflammatory conditions. Two lncRNAs associated with inflammation and PANoptosis during osteogenic differentiation were identified from sequencing data and Gene Expression Omnibus (GEO) databases. Their functionalities were analyzed using diverse bioinformatics methodologies, resulting in the construction of the lncRNA-miRNA-mRNA network. Among these, lncRNA (MIR17HG) showed a high correlation with PANoptosis. Bibliometric methods were employed to collect literature data on PANoptosis, and its components were inferred. PCR and Western Blotting experiments confirmed that lncRNA MIR17HG is related to PANoptosis in osteoblasts during inflammation. Conclusions Our data suggest that TNF-α-induced inhibition of osteogenic differentiation and PANoptosis in MC3T3-E1 osteoblasts is associated with MIR17HG. These findings highlight the critical role of MIR17HG in the interplay between inflammation, PANoptosis, and osteogenic differentiation, suggesting potential therapeutic targets for conditions involving impaired bone formation and inflammatory responses.

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Ecological risk of per-and polyfluorinated alkyl substances in the phytoremediation process: a case study for ecologically keystone species across two generations - Diga Gang; Huawei Jia; He Ji; Jingwen Li; Hongwei Yu; Chengzhi Hu; Jiuhui Qu (Science of The Total Environment, 2024)

Structure-dependent destructive adsorption of organophosphate flame retardants on lipid membranes - Bing Fang; Chunzhen Wang; Xuancheng Du; Guochao Sun; Bingqing Jia; Xiangdong Liu; Yuanyuan Qu; Qingmeng Zhang; Yanmei Yang; Yong-Qiang Li; Weifeng Li (Journal of Hazardous Materials, 2024)

The spatial overlapping regulated by nitrogen promotes the Spartina alterniflora potential invasion in coastal wetlands - Peng Jia; Guojuan Qu; Jing Jia; Changan Liu; Dezhi Li (Ocean & Coastal Management, 2024)

Photochemical transformation of liquid crystal monomers in simulated environmental media: Kinetics, mechanism, toxicity variation and QSAR modeling - Yandong Yang; Xiangkun Jiang; Yi Yang; Jia Wang; Yahui Zhao; Shanshan Lin; Jiao Qu; Christopher J. Martyniuk; Yuanhui Zhao; Chao Li (Water Research, 2024)

Spatiotemporal dynamics of reactive oxygen species and its effect on beta-blockers’ degradation in aquatic plants’ rhizosphere - He Ji; Jingwen Li; Diga Gang; Hongwei Yu; Hanzhong Jia; Chengzhi Hu; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Pyridinic-N induced reversible adsorption of high-boiling-point organic gases on functionalized mesoporous carbon - Qianyu Wang; Haoyang Wu; Yang Zhao; Bingya Xie; Mingli Qin; Chuanzhao Zhang; Baorui Jia; Yingshu Liu; Xuanhui Qu; Ralph T. Yang; Ziyi Li (Chemical Engineering Journal, 2024)

In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2024)

Numerical Simulation of Gas Production Behavior Using Radial Lateral Well and Horizontal Snake Well Depressurization Mining of Hydrate Reservoir in the Shenhu Sea Area of the South China Sea - Tinghui Wan; Mingming Wen; Hongfeng Lu; Zhanzhao Li; Zongheng Chen; Lieyu Tian; Qi Li; Jia Qu; Jingli Wang (Journal of Marine Science and Engineering, 2024)
Improving the production capacity of natural gas hydrates (NGHs) is crucial for their commercial development. Based on the data of the first on-site testing production of NGHs in the Shenhu Sea area, numerical methods were used to analyze the production behavior of radial lateral well (RLW) and horizontal snake well (HSW) with different completion lengths when they deployed at different layers of the Class-1 type hydrate reservoir (with a fixed pressure difference of 6 MPa and continuous production for 360 days). The results indicate that compared with the single vertical well production, RLW and HSW can effectively increase production capacity by enlarging drainage area and the productivity is directly proportional to the total completion length. The RLW and HSW deployed at the three-phase layer (TPL) have optimal mining performance within a 360-day production period. Different to the previous research findings, during a short-term production period of 360 days, regardless of the deployment layer, the overall production capacity of HSW is better than RLW’s. The total gas production of HSW-2 circles well type is about four times that of a single vertical well, reaching 1.554 × 107 ST m3. Moreover, the HSW-1 lateral well type stands out with an average Qg of 3.63 × 104 ST m3/d and a specific production index J of 16.93; it has the highest J-index among all well types, which means the best mining efficiency. It is recommended to choose the HSW-1 circle well type, if the coiled tubing drilling technique is used for on-site testing production of NGHs in the future. The research results provide insights into the potential applications of RLW and HSW in this sea area.

Numerical Simulation of Gas Production Behavior Using Stepwise Depressurization with a Vertical Well in the Shenhu Sea Area Hydrate Reservoir of the South China Sea - Tinghui Wan; Zhanzhao Li; Hongfeng Lu; Mingming Wen; Zongheng Chen; Lieyu Tian; Qi Li; Jia Qu; Jingli Wang (Journal of Marine Science and Engineering, 2024)
Stepwise depressurization is an important depressurization strategy in the development of natural gas hydrates. This work numerically analyzes the effects of different depressurization gradients and constant pressure durations on gas and water production during stepwise depressurization extraction with a vertical well in the Shenhu Sea area hydrate reservoir of the South China Sea. The results indicate that stepwise depressurization can reduce water production and raise the gas-to-water ratio in the early stages of production while ensuring cumulative gas output. When the vertical well is deployed at the model’s center with a completion length of 70 m and a constant pressure duration of 10 days, a depressurization gradient of 0.5 MPa, stepwise depressurization by 6 MPa, and continuous production for one year is achieved. Compared with direct depressurization, its cumulative gas production is 2.966 × 106 ST m3, which only decreases by 2.94%. However, it maintains a higher gas-to-water ratio in the early stages of production. Considering factors such as engineering operability, cumulative gas output, and gas-to-water ratio, it is recommended to use a small pressure gradient and a medium constant pressure stabilization time for stepwise depressurization Stepwise depressurization can maintain a high gas-to-water ratio while ensuring gas production and reducing water production can alleviate sand production problems and improve economic efficiency. The understanding gained from this work has reference value for the development of similar hydrate reservoirs worldwide.

PM2.5 exposure inhibits osteoblast differentiation by increasing the ubiquitination and degradation of Smad4 - Jiatao Yang; Chunqing Han; Junxing Ye; Xiping Hu; Ruijian Wang; Jin Shen; Longfei Li; Guoqin Hu; Xian Shi; Zhongtang Jia; Xiuxia Qu; Huanliang Liu; et al. (Toxicology Letters, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Exploring the carbon skeleton cycling regulation mechanism of single-wavelength light quality promoting the accumulation of polysaccharides in Spirulina platensis FACHB-439: Based on transcriptomics - Shuhong Li; Yonghong Tan; Zixi Wei; Wenjuan He; Zihan Qu; Tongliang Yang; Jia Shi; Yifu Zhang; Guiyun Chen; Chunfeng Song; Ye Chen (Journal of Cleaner Production, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Aconitum coreanum and processed products on its base prevent stroke via the PI3K/Akt and KEAP1/NRF2 in the in vivo study - Wan-ting Zeng; Li-ting Zhou; Ru Jia; Yue Liu; Qian Cai; Yang Qu (Metabolic Brain Disease, 2024)

Microbial mechanisms in nitrogen fertilization: Modulating the re-mobilization of clay mineral-bound cadmium in agricultural soils - Jun-Feng Wang; Can Liu; Zhi-Min Xu; Fo-Peng Wang; Yun-Yun Sun; Jia-Wei Huang; Qu-Sheng Li (Science of The Total Environment, 2024)

Increased risk of heavy metal accumulation in mangrove seedlings in coastal wetland environments due to microplastic inflow - Jia-Wei Huang; Yun-Yun Sun; Qu-Sheng Li; Huan-Zhan Zhou; Yi-Hao Li; Xiang-Xiang Fan; Jun-Feng Wang (Environmental Pollution, 2024)

Anisotropic materials based on carbohydrate polymers: A review of fabrication strategies, properties, and applications - Qi An; Jingnan Ren; Xiao Jia; Shasha Qu; Nawei Zhang; Xiao Li; Gang Fan; Siyi Pan; Zhifeng Zhang; Kangning Wu (Carbohydrate Polymers, 2024)

Numerical Simulation of Production Behavior with Different Complex Structure Well Types in Class 1-Type Hydrate Reservoir - Tinghui Wan; Zhanzhao Li; Mingming Wen; Zongheng Chen; Lieyu Tian; Qi Li; Jia Qu; Jingli Wang (Journal of Marine Science and Engineering, 2024)
Enhancing the production capacity of natural gas hydrates (NGHs) is critical for its commercial development. Complex structure wells may efficiently increase drainage areas while enhancing exploitation efficiency. Based on the field data of China’s first offshore NGH test production, the numerical method was used to analyze the production performance of different complex structure well types by continuous depressurization production for 360 days under the preconditions of fixed effective completion length of 300 m and a pressure difference of 6 MPa. Results indicated that the complex structure well types deployed at the three-phase layer demonstrated superior production performance within 240 days of production; the DLW2 and HW2 well types stood out, with an average gas production rate Qg reaching 43,333 m3/d and a specific production index J of 24.1. After 360 days of production, benefiting from multi-layer combined production, the Cluster vertical well deployed at the multi-layer had the best production performance, with an average Qg of 34,444 m3/d and a J-index of 19.1. The research results provided insights into the complex structure well-type selection strategy for NGH depressurization in this sea area.

Signalling between the sexes during pollen tube reception - Alice L. Baillie; Jen Sloan; Li-Jia Qu; Lisa M. Smith (Trends in Plant Science, 2024)

Ocean acidification alters shellfish-algae nutritional value and delivery - Ruolan Jia; Minghao Yin; Xue Feng; Chengzhuang Chen; Chunfeng Qu; Ling Liu; Ping Li; Zhi-Hua Li (Science of The Total Environment, 2024)

Separation and quantification of tire and road wear particles in road dust samples: Bonded-sulfur as a novel marker - Yifan Ren; Wenhui Li; Qi Jia; Yanjun Zhao; Chen Qu; Li Liu; Jiemin Liu; Chuandong Wu (Journal of Hazardous Materials, 2024)

Effect of different defects on the competitive adsorption of formaldehyde and water on the surface of carbon materials: Density functional theory study - Zhonghua Wang; Zekun Sun; Haiqian Zhao; Jun Li; Xing Zhang; Jiuyang Jia; Kaibo An; Ziyu Tang; Mingqi He; Zhibin Qu (Science of The Total Environment, 2024)

Simultaneous degradation of NSAIDs in aqueous and sludge stages by an electron-Fenton system derived from sediment microbial fuel cell based on a novel Fe@Mn biochar GDC - Shuai Zhao; Hanyan Li; Jia Zhou; Tawatchai Sumpradit; El-Sayed Salama; Xiangkai Li; Jianhang Qu (Chemical Engineering Journal, 2024)

Enhanced peroxymonosulfate activation via heteroatomic doping defects of pyridinic and pyrrolic N in 2D N‑doped carbon nanosheets for BPA degradation - Guojuan Qu; Peng Jia; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

Combustion derived carbon with ultrahigh-mesoporosity and moderate surface affinity towards reversible low-volatile gas capture - Qianyu Wang; Haoyang Wu; Mingli Qin; Yang Zhao; Chuanzhao Zhang; Shiqi Zhou; Baorui Jia; Yingshu Liu; Xuanhui Qu; Ralph T. Yang; Ziyi Li (Chemical Engineering Journal, 2024)

Numerical simulation of hydrodynamic performance of pump-jet propulsor with serrated trailing-edge duct under different working conditions - Yu Sun; Li-xin Qu; Huang-hua Peng; Jia-min Guo; Zhi-xin Xiong (Ocean Engineering, 2023)

Charge characteristics of guar gums on the three-stage interaction mechanism with mucin to improve the mucoadhesion ability - Minghao Zhang; Yuanyuan Qu; Jinlong Li; Lijun Yin; Qingrong Huang; Xin Jia (Food Hydrocolloids, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Synergistic activation of peroxymonosulfate by intrinsic defect and graphitic N of N, P co-doped carbon microspheres for BPA degradation - Guojuan Qu; Peng Jia; Tao Zhang; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Chemical Engineering Journal, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Nano-elemental selenium particle developed via supramolecular self-assembly of chondroitin sulfate A and Na2SeO3 to repair cartilage lesions - Jing Han; Huan Deng; Yang Li; Lichun Qiao; Hongrui Jia; Lan Zhang; Linghang Wang; Chengjuan Qu (Carbohydrate Polymers, 2023)

A new strategy to study geochemical characteristics and migration of crude oils in Zhu I Depression, Pearl River Mouth Basin, South China Sea - Xuanbo Gao; Siyuan Di; Xianfeng Tan; Wanfeng Zhang; Jia Wang; Long Luo; Xuejiao Qu; Jianping Liu; Shengyu Li; Nan Jiang; Sheng He; Shukui Zhu (Organic Geochemistry, 2023)

Effects of climate change and anthropogenic activity on ranges of vertebrate species endemic to the Qinghai–Tibet Plateau over 40 years - Dechun Jiang; Xumao Zhao; Jordi López‐Pujol; Zhiqiang Wang; Yanhua Qu; Yanming Zhang; Tongzuo Zhang; Dayong Li; Ke Jiang; Bin Wang; Chaochao Yan; Jia‐Tang Li (Conservation Biology, 2023)
Over the past 40 years, the climate has been changing and human disturbance has increased in the vast Qinghai–Tibet Plateau (QTP). These 2 factors are expected to affect the distribution of a large number of endemic vertebrate species. However, quantitative relationships between range shifts and climate change and human disturbance of these species in the QTP have rarely been evaluated. We used occurrence records of 19 terrestrial vertebrate species (birds, mammals, amphibians, and reptiles) occurring in the QTP from 1980 to 2020 to quantify the effects of climate change and anthropogenic impacts on the distribution of these 4 taxonomic groups and estimated species range changes in each species. The trend in distribution changes differed among the taxonomic groups, although, generally, ranges shifted to central QTP. Climate change contributed more to range variation than human disturbance (the sum of the 4 climatic variables contributed more than the sum of the 4 human disturbance variables for all 4 taxonomic groups). Suitable geographic range increased for most mammals, amphibians, and reptiles (+27.6%, +18.4%, and +27.8% on average, respectively), whereas for birds range decreased on average by 0.9%. Quantitative evidence for climate change and human disturbance associations with range changes for endemic vertebrate species in the QTP can provide useful insights into biodiversity conservation under changing environments.

Influence of Excavation Pits on the Wave Hydrodynamics of Fringing Reefs under Regular Waves - Xu Wang; Ke Qu; Jia Men; Liangbin Zhang; Junjie Li; Rongze Gao (Journal of Marine Science and Engineering, 2023)
Dredging materials from reef flats have become an important source of sand and aggregates for meeting the infrastructure needs of coral-lined shores in subtropical and tropical regions, especially for low-lying atoll islands. Dredging at the reef flats can generate artificial excavation pits, which not only have profound influences on coral ecological stability but also deeply affect the hydrodynamic characteristics of coral reefs. To deepen the understanding of the influence of excavation on the wave hydrodynamics of fringing reefs, the wave propagation, wave transformation, wave setup, and wave runup processes of regular waves on fringing reefs with artificial pits have been systematically analyzed using a non-hydrostatic numerical wave solver (NHWAVE). The effects of some significant factors have been carefully investigated. According to the study findings, the existence of artificial pits can result in a slight decrease in the wave height around the artificial pit. The time-mean maximum of wave runup height at the backreef slope can be reduced to some extent when the artificial pit is present. When placed close to the reef edge, the artificial pit can have noticeable effects on the hydrodynamic characteristics of fringing reefs, particularly the wave setup along the reef flat. It is hoped that the study findings can provide further reference for evaluation of the influences of artificial pits on the wave hydrodynamics of fringing reefs.

Comparative life cycle assessment of the linear and circular wine industry chains: a case study in Inner Mongolia, China - Jing Liu; Chonglei Li; Yuting Qu; Zhibin Jia; Jinhua Li (Environmental Science and Pollution Research, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Seismic response study of a steel lattice transmission tower considering the hysteresis characteristics of bolt joint slippage - Jia-Xiang Li; Jin-Peng Cheng; Chao Zhang; Chun-Xu Qu; Xiao-Hong Zhang; Wen-Qiang Jiang (Engineering Structures, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Microplastics distribution and microbial community characteristics of farmland soil under different mulch methods - Na-ying Li; Jia-hui Qu; Jin-yan Yang (Journal of Hazardous Materials, 2023)

Deciphering the microbial community tolerance mechanism and alteration of antibiotic resistance genes during chloramphenicol wastewater treatment - Jia Zhou; Yan Chen; Wan-Xia Li; Jian-Hang Qu; Tian Chen; Yi-Ping Wang; Ning-Yu Geng (International Biodeterioration & Biodegradation, 2023)

Numerical investigation on vortex control effect of pump-jet propulsion via porous blade tips - Yu Sun; Li-xin Qu; Geng Wang; Huang-hua Peng; Jia-min Guo (Ocean Engineering, 2023)

Air pollutant emissions and reduction potentials from municipal solid waste incineration in China - Ling Tang; Jing Guo; Ruxing Wan; Min Jia; Jiabao Qu; Ling Li; Xin Bo (Environmental Pollution, 2023)

Temperature dependence of volatile organic compound emissions from surface coatings: Inter-species difference observed in real indoor environments and mechanistic understanding - Jia Qiu; Di Xie; Yatai Li; Yuekun Qu; Ying Liu; Tong Zhu; Jianyin Xiong; Yingjun Liu (Building and Environment, 2023)

Numerical Investigation on Hydrodynamic Processes of Extreme Wave Groups on Fringing Reef - Ke Qu; Jia Men; Xu Wang; Xiaohan Li (Journal of Marine Science and Engineering, 2023)
The low-lying reef islands distributed in the tropical and subtropical coastal regions are highly vulnerable to the devastating damages of surges and waves during the severe weather events. Over the past two decades, extreme waves have caused tremendous loss and damages to the tropical and subtropical coastal regions. Previous research has focused on the wave hydrodynamics of tsunami waves, as well as regular and irregular waves on the fringing reefs. The complex wave hydrodynamics of extreme waves on the fringing reefs are rarely studied. By applying the nonhydrostatic numerical flow solver (NHWAVE), transformation and breaking process of the crest- and trough-focused wave groups on the fringing reef are analyzed in this study. Influences of the major factors, i.e., water depth, significant wave height, peak wave period, forereef slope and backreef slope, and ridge width, are discussed in detail. The results show that there are complex interactions between the fringing reef and the focused wave group. Breaking waves of high intensity can form at the reef crest. Meanwhile, due to the wave breakings at the reef crest and bottom friction of the reef flat, the local wave height can be effectively reduced. Within the complex wave hydrodynamics of focused waves on the fringing reef, most of the wave energy can be dissipated. In addition, hydrodynamic difference between the crest- and trough-focused waves on the fringing reef is very limited. The research results of this study will further help researchers to better understand the wave hydrodynamics of extreme waves over the fringing reefs.

Building a satisfactory indoor environment for healthcare facility occupants: A literature review - Xiumei Shen; Hong Zhang; Ying Li; Kaichen Qu; Liang Zhao; Guangyan Kong; Wenzhao Jia (Building and Environment, 2023)

Development of A Novel Adaptive Range Strain Sensor for Structural Crack Monitoring - Ziguang Jia; Guangda Ma; Xin Su; Yibo Li; Chenghao Xing; Shuhan Ye; Xuan Yi; Chunxu Qu (Journal of Marine Science and Engineering, 2022)
Ocean platforms that are under complex sea conditions and loads for long periods are prone to fatigue cracks. These cracks may lead to large deformations, even displacement, of the platform, and should be monitored to ensure engineering safety. Cracks are not easily detected in the micro stage and small levels of strain measurement are required to ensure high accuracy. Furthermore, cracks are prone to suddenly developing into large deformations, especially in structural connections in practical engineering. This study developed a novel adaptive range strain sensor for structural crack monitoring that can monitor the whole structural crack propagation process in ocean platforms. The strain sensor is used for micro deformation monitoring through its fiber Bragg grating (FBG) sensor with high sensitivity. The sensor can automatically adapt to crack fractures and provide warnings through an STM32 single-chip microcomputer (SCM) system when the structure suddenly cracks, causing large deformation. The experimental results demonstrate that the device has high precision in micro measurement with the ability to capture structural fractures. The field application shows the high strain sensitivity of the sensor in crack monitoring, which indicates that the adaptive range strain sensor is suitable for the structural crack monitoring of ocean platforms.

Comprehensive risk assessment of algae and shellfish in the middle route of South-to-North Water Diversion Project - Yan Long; Mengjuan Feng; Youming Li; Jia Qu; Wei Gao (Environmental Science and Pollution Research, 2022)

Palmitoylation of MDH2 by ZDHHC18 activates mitochondrial respiration and accelerates ovarian cancer growth - Xuan Pei; Kai-Yue Li; Yuan Shen; Jin-Tao Li; Ming-Zhu Lei; Cai-Yun Fang; Hao-Jie Lu; Hui-Juan Yang; Wenyu Wen; Miao Yin; Jia Qu; Qun-Ying Lei (Science China Life Sciences, 2022)

Phylogenetic relationships and migration patterns of the Fargesia spathacea complex inferred from genomic data - Wan-Wan Li; Yun Zhou; Lei Huang; Yu‐Qu Zhang; Yi Ren; Jia-Ning Yu (Plant Systematics and Evolution, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

A Highly Selective Fluorescent Probe for the Detection of Nitroreductase Based on a Naphthalimide Scaffold - Han Li; Feng Jintao; Zhen Wang; Yan Jia; Peng Li; Cuixia Yao; Zongjin Qu (Journal of Fluorescence, 2022)

Celsr3 Inactivation in the Brainstem Impairs Rubrospinal Tract Development and Mouse Behaviors in Motor Coordination and Mechanic-Induced Response - Boli Chen; Fuxiang Li; Bin Jia; Kwok-Fai So; Ji-An Wei; Yuchu Liu; Yibo Qu; Libing Zhou (Molecular Neurobiology, 2022)
Inactivation of Celsr3 in the forebrain results in defects of longitudinal axonal tracts such as the corticospinal tract. In this study, we inactivated Celsr3 in the brainstem using En1-Cre mice ( Celsr3 cKO) and analyzed axonal and behavioral phenotypes. Celsr3 cKO animals showed an 83% reduction of rubrospinal axons and 30% decrease of corticospinal axons in spinal segments, associated with increased branching of dopaminergic fibers in the ventral horn. Decreases of spinal motoneurons, neuromuscular junctions, and electromyographic signal amplitude of the biceps were also found in mutant animals. Mutant mice had impaired motor coordination and defective response to heavy mechanical stimulation, but no disability in walking and food pellet handling. Transsynaptic tracing demonstrated that rubrospinal axons synapse on spinal neurons in the deep layer of the dorsal horn, and mechanical stimulation of hindpaws induced strong calcium signal of red nuclei in control mice, which was less prominent in mutant mice. In conclusion, Celsr3 regulates development of spinal descending axons and the motor network in cell and non-cell autonomous manners, and the maturation of the rubrospinal system is required for motor coordination and response to mechanical stimulation.

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Differences of carbon and nitrogen stoichiometry between different habitats in two natural Korean pine forests in Northeast China’s mountainous areas - Ya-fei Wang; Wen-biao Duan; Mei-xue Qu; Li-xin Chen; Hang-yu Lan; Xi-feng Yang; Si-jing Meng; Jia Chen (Journal of Mountain Science, 2022)

Functional connectivity alteration of the deprived auditory regions with cognitive networks in deaf and inattentive adolescents - Jianhong Li; Weiwei Men; Jia-Hong Gao; Yang Wang; Xiaoxia Qu; David Chao Dong Zhu; Junfang Xian (Brain Imaging and Behavior, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Dynamically monitoring cellular γ-H2AX reveals the potential of carcinogenicity evaluation for genotoxic compounds - Minmin Qu; Hua Xu; Wuju Li; Jia Chen; Yajiao Zhang; Bin Xu; Zhi Li; Tao Liu; Lei Guo; Jianwei Xie (Archives of Toxicology, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

A Fluorescent Visual Proton Donor and Photoacid Sterilant Based on Sulfonate‐conjugated BODIPY - Abbas Mohammed Ali; Jian Shao; Jia-Xin Wang; Qiu-Yun Chen; Yang Li; Ling-Ling Qu (Journal of Fluorescence, 2021)

Comparative transcriptomic and metabolomic analyses of carotenoid biosynthesis reveal the basis of white petal color in Brassica napus - Ledong Jia; Junsheng Wang; Rui Wang; Mouzheng Duan; Cailin Qiao; Xue Chen; Guoqiang Ma; Xintong Zhou; Meichen Zhu; Fuyu Jing; Shengsen Zhang; Cunmin Qu; et al. (Planta, 2021)
Main conclusion The molecular mechanism underlying white petal color in Brassica napus was revealed by transcriptomic and metabolomic analyses. Abstract Rapeseed ( Brassica napus L.) is one of the most important oilseed crops worldwide, but the mechanisms underlying flower color in this crop are known less. Here, we performed metabolomic and transcriptomic analyses of the yellow-flowered rapeseed cultivar ‘Zhongshuang 11’ (ZS11) and the white-flowered inbred line ‘White Petal’ (WP). The total carotenoid contents were 1.778-fold and 1.969-fold higher in ZS11 vs. WP petals at stages S2 and S4, respectively. Our findings suggest that white petal color in WP flowers is primarily due to decreased lutein and zeaxanthin contents. Transcriptome analysis revealed 10,116 differentially expressed genes with a fourfold or greater change in expression ( P -value less than 0.001) in WP vs. ZS11 petals, including 1,209 genes that were differentially expressed at four different stages and 20 genes in the carotenoid metabolism pathway. BnNCED4b , encoding a protein involved in carotenoid degradation, was expressed at abnormally high levels in WP petals, suggesting it might play a key role in white petal formation. The results of qRT-PCR were consistent with the transcriptome data. The results of this study provide important insights into the molecular mechanisms of the carotenoid metabolic pathway in rapeseed petals, and the candidate genes identified in this study provide a resource for the creation of new B. napus germplasms with different petal colors.

Physical simulation experiment on porosity evolution and controlling factors of Miocene reservoir in Ledong-Lingshui Depression, Qiongdongnan Basin, South China Sea - Xiyu Qu; Yangchen Zhang; Xiu Chen; Xibing Yang; Li You; Jia Zhong (Arabian Journal of Geosciences, 2020)

MicroRNA-153-3p enhances the sensitivity of chronic myeloid leukemia cells to imatinib by inhibiting B-cell lymphoma-2-mediated autophagy - Yu-Ling Li; Jia-Ming Tang; Xiao-Yun Chen; Bing Luo; Guo-Hua Liang; Qian Qu; Zi-Yuan Lu (Human Cell, 2020)

Community structure of Anaeromyxobacter in Fe(III) reducing enriched cultures of paddy soils - Kun Wang; Rong Jia; Lina Li; Rui Jiang; Dong Qu (Journal of Soils and Sediments, 2020)

A modified protein persulfidation detection method - Z. Q. Liu; Y. Q. Jia; Y. W. Li; C. Y. Cao; J. J. Qu; Yanxi Pei (Acta Physiologiae Plantarum, 2020)

Spontaneous mutations in FgSAD1 suppress the growth defect of the Fgprp4 mutant by affecting tri‐snRNP stability and its docking in Fusarium graminearum - Xiaoping Li; Zhili Fan; Ming Yan; Jia Qu; Jin‐Rong Xu; Qiaojun Jin (Environmental Microbiology, 2019)
Summary FgPrp4, the only kinase in the spliceosome, is not essential for viability, but is important for splicing efficiency in Fusarium graminearum . The Fgprp4 deletion mutant had severe growth defects but often produced spontaneous suppressors with faster growth rate. To better understand the suppression mechanism, we identified and characterized spontaneous mutations in the tri‐snRNP‐specific protein, FgSad1, which suppressed the growth defects of Fgprp4 . The L512P mutation was verified for its suppressive effects on Fgprp4 , suggesting that mutations in FgSad1 may have effects involving FgPrp4 phosphorylation on FgSad1. Phosphoproteomics analysis showed that FgSad1 may not be the direct substrate of FgPrp4 kinase. Furthermore, truncation analysis showed that the N‐terminal, extra RS‐rich region of FgSad1 is critical for its function and is post‐translationally modified. The P258S or S269P mutations in FgSad1 increased its interactions with the U5 protein FgPrp8 and the U4/U6 protein FgPrp31, which may result in tri‐snRNP stabilization. Additionally, the D76N mutation increased the association of FgSad1 with the U2 snRNP. These data indicate that suppressor mutations in FgSad1 increase the stability of the tri‐snRNP and/or the affinity of FgSad1 with U2 snRNP and therefore potentially facilitate the docking of tri‐snRNP into the spliceosome.

Serratia microhaemolytica sp. nov., isolated from an artificial lake in Southern China - Juan Wang; Min-Ling Zheng; Jian-Yu Jiao; Wei-Jia Wang; Shuai Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Cysteine-rich peptides: signals for pollen tube guidance, species isolation and beyond - Sheng Zhong; Li-Jia Qu (Science China Life Sciences, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

The complete genome of the antifungal bacterium Pseudomonas sp. strain MS82 - Lin Ma; Shaoxuan Qu; Jinsheng Lin; Jiayuan Jia; Sonya M. Baird; Ning Jiang; Huiping Li; Lijuan Hou; Shi-En Lu (Journal of Plant Diseases and Protection, 2019)

The response of metabolically active Clostridium community to initial pH shift is closely correlated with microbial Fe(III) reduction in flooded paddy soils - Lina Li; Zhi Qu; Baoli Wang; Rong Jia; Dong Qu (Journal of Soils and Sediments, 2019)

Modification of PPTA-based polymeric waste and adsorption properties for metal ions - J. J. Gao; R. J. Qu; S. S. Li; F. W. Pan; X. H. Jia; C. M. Sun; Y. Zhang; Q. L. Ma; C. X. Li (International Journal of Environmental Science and Technology, 2018)

Effects of body mass index on the outcomes of in vitro fertilization in Chinese patients with polycystic ovary syndrome: a retrospective cohort study - Xiao-ming Pan; Zhong Lin; Nan Li; Jia-qi Wu; Dan-qing Chen; Yi-min Zhu; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2018)

Analysis and Risk Assessment of Seven Toxic Element Residues in Raw Bovine Milk in China - Xue-Yin Qu; Nan Zheng; Xue-Wei Zhou; Song-Li Li; Jia-Qi Wang; Wen-Ju Zhang (Biological Trace Element Research, 2018)

Complementary feeding patterns among ethnic groups in rural western China - Peng-fei Qu; Ya Zhang; Jia-mei Li; Ruo Zhang; Jiao-mei Yang; Fang-liang Lei; Shan-shan Li; Dan-meng Liu; Shao-nong Dang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2018)

Enhanced iron(III) reduction following amendment of paddy soils with biochar and glucose modified biochar - Rong Jia; Lina Li; Dong Qu; Nana Mi (Environmental Science and Pollution Research, 2018)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Changes and relations of photosynthesis and iron cycling in anoxic paddy soil amended with high concentrations of sulfate - Qin Chen; Rong Jia; Dong Qu; Ming Li (Environmental Science and Pollution Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

Expression of KCNA5 Protein in Human Mammary Epithelial Cell Line Associated with Caveolin-1 - Jia Liu; Chao Qu; Hongyan Li; Yejun Zhang; Jia Sun; Shuo Yang; Jing Liu; Lijia An; Wei Zou (The Journal of Membrane Biology, 2016)

Effect of operation parameters on the flux stabilization of gravity-driven membrane (GDM) filtration system for decentralized water supply - Xiaobin Tang; An Ding; Fangshu Qu; Ruibao Jia; Haiqing Chang; Xiaoxiang Cheng; Bin Liu; Guibai Li; Heng Liang (Environmental Science and Pollution Research, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

Characterizing the compositional variation of dissolved organic matter over hydrophobicity and polarity using fluorescence spectra combined with principal component analysis and two-dimensional correlation technique - Ben-Sheng Su; Zhen Qu; Xiao-Song He; Ying-Hao Song; Li-Min Jia (Environmental Science and Pollution Research, 2016)

The transcription factor TBX2 regulates melanogenesis in melanocytes by repressing Oca2 - Yu Chen; Li Pan; Zhongyuan Su; Jing Wang; Huirong Li; Xiaoyin Ma; Yin Liu; Fan Lu; Jia Qu; Ling Hou (Molecular and Cellular Biochemistry, 2016)

Combination of PPT with LiCl Treatment Prevented Bilateral Ovariectomy-Induced Hippocampal-Dependent Cognition Deficit in Rats - Na Qu; Xiang-Yu Zhou; Li Han; Lei Wang; Jia-Xin Xu; Teng Zhang; Jiang Chu; Qiao Chen; Jian-Zhi Wang; Qi Zhang; Qing Tian (Molecular Neurobiology, 2016)

Necroptosis: a potential, promising target and switch in acute pancreatitis - Gang Wang; Feng-Zhi Qu; Le Li; Jia-Chen Lv; Bei Sun (Apoptosis, 2016)

The antibacterial mechanism of berberine against Actinobacillus pleuropneumoniae - Shuai Kang; Zhengwen Li; Zhongqiong Yin; Renyong Jia; Xu Song; Li Li; Zhenzhen Chen; Lianci Peng; Jing Qu; Zhiqiang Hu; Xin Lai; Guangxi Wang; et al. (Natural Product Research, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Erratum to: pH shift-mediated dehydrogenation and hydrogen production are responsible for microbial iron(III) reduction in submerged paddy soils - Rong Jia; Li-Na Li; Dong Qu (Journal of Soils and Sediments, 2015)

pH shift-mediated dehydrogenation and hydrogen production are responsible for microbial iron(III) reduction in submerged paddy soils - Rong Jia; Li-Na Li; Dong Qu (Journal of Soils and Sediments, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Matrix Metalloproteinase-14 Expression and Its Prognostic Value in Cervical Carcinoma - Huayi Wang; Xianhua Zhang; Liming Huang; Jia Li; Shuyun Qu; Fenglian Pan (Cell Biochemistry and Biophysics, 2014)

An α-glucan isolated from root of Isatis Indigotica, its structure and adjuvant activity - Junjie Shan; Guohui Sun; Jinwei Ren; Ting Zhu; Peiyuan Jia; Wensheng Qu; Qian Li; Junhua Wu; Hao Ma; Song Wen; Yuxia Wang (Glycoconjugate Journal, 2014)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Construction of EGFP-Labeling System for Visualizing the Infection Process of Xanthomonas axonopodis pv. citri in planta - Li-Ping Liu; Zi-Niu Deng; Jin-Wang Qu; Jia-Wen Yan; Vittoria Catara; Da-Zhi Li; Gui-You Long; Na Li (Current Microbiology, 2012)

Functional conservation of the plant EMBRYONIC FLOWER2 gene between bamboo and Arabidopsis - Hong Xu; Ling-Jing Chen; Li-Jia Qu; Hong-Ya Gu; De-Zhu Li (Biotechnology Letters, 2010)

Fluorescent Biological Label for Recognizing Human Ovarian Tumor Cells Based on Fluorescent Nanoparticles - Shasheng Huang; Ruina Li; Yongxia Qu; Jian Shen; Jia Liu (Journal of Fluorescence, 2009)

Involvement of an R2R3-MYB transcription factor gene AtMYB118 in embryogenesis in Arabidopsis - Yunfei Zhang; Guangyu Cao; Li-Jia Qu; Hongya Gu (Plant Cell Reports, 2009)

The possible action mechanisms of indole-3-acetic acid methyl ester in Arabidopsis - Linchuan Li; Xianhui Hou; Tomohiko Tsuge; Maoyu Ding; Takashi Aoyama; Atsuhiro Oka; Hongya Gu; Yunde Zhao; Li-Jia Qu (Plant Cell Reports, 2008)

A gain-of-function mutation of transcriptional factor PTL results in curly leaves, dwarfism and male sterility by affecting auxin homeostasis - Xin Li; Genji Qin; Zhangliang Chen; Hongya Gu; Li-Jia Qu (Plant Molecular Biology, 2008)

Identification and characterization of COI1-dependent transcription factor genes involved in JA-mediated response to wounding in Arabidopsis plants - Zhe Wang; Guangyu Cao; Xinlei Wang; Jin Miao; Xiaoting Liu; Zhangliang Chen; Li-Jia Qu; Hongya Gu (Plant Cell Reports, 2007)

The MYB Transcription Factor Superfamily of Arabidopsis: Expression Analysis and Phylogenetic Comparison with the Rice MYB Family - Chen Yanhui; Yang Xiaoyuan; He Kun; Liu Meihua; Li Jigang; Gao Zhaofeng; Lin Zhiqiang; Zhang Yunfei; Wang Xiaoxiao; Qiu Xiaoming; Shen Yunping; Zhang Li; et al. (Plant Molecular Biology, 2006)

A deletion mutation in the ?A1/A3 crystallin gene (CRYBA1/A3) is associated with autosomal dominant congenital nuclear cataract in a Chinese family - Yanhua Qi; Hongyan Jia; Shangzhi Huang; Hui Lin; Jingzhi Gu; Hong Su; Tieying Zhang; Ya Gao; Lijun Qu; Dandan Li; Ying Li (Human Genetics, 2004)

Molecular mapping of the reverse thermo-sensitive genic male-sterile gene (rtms1) in rice - J. H. Jia; D. S. Zhang; C. Y. Li; X. P. Qu; S. W. Wang; V. Chamarerk; H. T. Nguyen; B. Wang (Theoretical and Applied Genetics, 2001)

Recovery of transgenic orchid plants with hygromycin selection by particle bombardment to protocorms - Zhihua Yu; Minyong Chen; Lin Nie; Huafei Lu; Xiaotian Ming; Honghong Zheng; Li-Jia Qu; Zhangliang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Plant Molecular Biology in China - Chen Zhangliang; Qu Li-Jia (Plant Molecular Biology Reporter, 1997)